(untitled) (Al-Qamar, 2021)
The purpose of the current research is to examine the impact of employability skills on the Islamic bank’s performance in Pakistan. The study empirically based on the primary data collection via survey-based research instrument from 249 Islamic bankers of five Islamic banks and six conventional banks having more than 100 Islamic branches in Pakistan. The empirical results revealed that interpersonal skills, social skills, technical skills and subject knowledge have a positive and significant relationship with organizational performance in the Islamic banking sector of Pakistan. The skilled human resources availability is the need for a significantly growing Islamic banking and finance industry. The education for employability focuses not only on development of employability skills but also on subject-specific knowledge acquisition required for the existing dynamic business settings. Policy-makers, the university administration, employers, and graduates should actively find ways to enhance employability skills by identifying and encouraging the best practices for successful employability initiatives.